2022
DOI: 10.21037/jtd-22-707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24-hour postoperative intravenous fluid on postoperative outcomes after lobectomy: a retrospective observational study

Abstract: Background: Postoperative fluid management plays a key role in providing adequate tissue perfusion, stabilizing hemodynamics, and reducing morbidities related to hemodynamics. This study evaluated the dose-response relationship between postoperative 24-hour intravenous fluid volume and postoperative outcomes in patients with non-small cell lung cancer (NSCLC) undergoing video-assisted thoracoscopic surgery (VATS) lobectomy. Methods: A retrospective analysis of adult patients with NSCLC undergoing VATS lobectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Little has been published about postoperative IV fluid infusions after thoracic surgery. One study showed that infusions of more than 1410 ml/24 h were associated with PPCs, as were infusion rates of less than 1080 ml/24 h [41]. However, it is difficult to know how to interpret these results as the intraoperative fluid infusion rates were high (around 12 ml/kg/hour) and oral fluids and diet were not resumed until 6–8 h after surgery.…”
Section: Postoperative Fluid Managementmentioning
confidence: 99%
“…Little has been published about postoperative IV fluid infusions after thoracic surgery. One study showed that infusions of more than 1410 ml/24 h were associated with PPCs, as were infusion rates of less than 1080 ml/24 h [41]. However, it is difficult to know how to interpret these results as the intraoperative fluid infusion rates were high (around 12 ml/kg/hour) and oral fluids and diet were not resumed until 6–8 h after surgery.…”
Section: Postoperative Fluid Managementmentioning
confidence: 99%